2013
DOI: 10.1007/s11596-013-1192-x
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of parameters for preparation of docetaxel-loaded PLGA nanoparticles by nanoprecipitation method

Abstract: The purpose of this study was to develop docetaxel-poly (lactide-co-glycolide) (PLGA) loaded nanoparticles by using nanoprecipitation method and optimize the relative parameters to obtain nanoparticles with higher encapsulation efficiency and smaller size. The physicochemical characteristics of nanoparticles were studied. The optimized parameters were as follows: the oil phase was mixture of acetone and ethanol, concentration of tocopheryl polyethylene glycol succinate (TPGS) was 0.2%, the ratio of oil phase t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 29 publications
3
15
0
Order By: Relevance
“…SE-NPs exhibited higher entrapment efficiency than NR-NPs; this just corresponds to the results confirmed by several researchers [41,42]. We thought that this may be due to the larger size of SE-NP than NR-NP which could support a larger space for Sal encapsulation.…”
Section: Resultssupporting
confidence: 89%
“…SE-NPs exhibited higher entrapment efficiency than NR-NPs; this just corresponds to the results confirmed by several researchers [41,42]. We thought that this may be due to the larger size of SE-NP than NR-NP which could support a larger space for Sal encapsulation.…”
Section: Resultssupporting
confidence: 89%
“…It should be emphasized that determining the amount of loaded drug inside polymeric matrix is a crucial step in characterization of nanoparticle. To date, docetaxel has been quantitatively assayed by means of different HPLC [15]- [17] [41] or UV [18] set-ups reporting different assay outcomes. for instance, Esmaeili et al [12] reported their method LOD to be 50 ng/ml with a retention time around 12 min.…”
Section: Nanoparticle Drug Loading and Encapsulation Efficiencymentioning
confidence: 99%
“…Actually, AuNPs seem to be the most promising in this field. Shi et al [164] reported that deposition of AuNPs into fibrous decellularized matrices improved resulting morphology of cardiac cells grown within these scaffolds. This provides better striation behavior and improved electrical coupling of proteins.…”
Section: Electrical Propertiesmentioning
confidence: 99%